Comparison between talazoparib and conventional chemotherapy in the treatment of HER2-positive breast cancer patients: A retrospective study - Wang, Ning; Yu, Xiaopeng (Frontiers in Immunology, 2022)
Background: The benefits of talazoparib compared with chemotherapy in HER2-negative advanced breast cancer (ABC) remain unclear. Methods: Patients older than 18 years, with a deleterious germline BRCA1/2 (gBRCA1/2) mutated, metastatic, or locally advanced and HER2-positive breast cancer were enrolled. Patient data including age, menopausal status, tumor grade, 2 pathologic tumor size, lymph node status, and whether they had received adjuvant radiation or chemotherapy was collected. The primary outcomes of the study were disease-free survival (DFS), which was defined as the time from randomization to death or recurrence due to any reason, and overall survival (OS), which was defined as the time from randomization to death due to any reason. P<0.05 was considered to be statistically significant. Results: A total of 136 patients were finally enrolled in the present retrospective study, including 62 patients in the talazoparib group (group A) and 74 in the chemotherapy group (group B). After a median follow-up of 70.9 months [95% confidence interval (CI): 68.3–78.5], both DFS and OS did not differ significantly between the two groups (P=0.658 and P=0.690, respectively). The exploratory subgroup analyses further validated the robustness of the primary results across the subgroups. Conclusions: Talazoparib was not better than chemotherapy in terms of DFS and OS for the treatment of gBRCA1/2 mutated HER2-positive breast cancer patients.